Model of Relationship Marketing and E-Commerce in Improving Marketing Performance of Batik SMEs - Farida, Naili; Naryoso, Agus; Yuniawan, Ahyar (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
Various models of relationship marketing were developed with the aim to create sustainable performance. Old model of marketing is a conventional marketing that only rely on face to face marketing. However, in line with the advances in market information technology, customers should be pampered and served well. E-commerce and E-business is the application of busi-ness operations conducted through the Internet so that it can expand product marketing both in national and international markets. The purpose of this study is to develop and test models of relationship marketing, that is, the relationship among determinants of marketing performance increase. Sample in this study is 41 Batik SME owners in Semarang City. The analysis used in this study is the SEM-PLS. Data processing in this study uses the Smart PLS. The results of this study indicate that: (1) social capital has no influence on market capabilities; (2) relation-ship quality has influence on market capabilities; (3) entrepreneurial orientation has influence on social capital; (4) market capabilities has influence on marketing performance; (5) e-com-merce has influence on marketing performance, meaning that a better e-commerce or online marketing will be able to improve the marketing performance of SMEs.